Evaluation of sputum eosinophil count as a predictor of treatment response to mepolizumab. Issue 2 (3rd May 2022) - Pavord, Ian D.; Buhl, Roland; Kraft, Monica; Prazma, Charlene M.; Price, Robert G.; Howarth, Peter H.; Yancey, Steven W.
For patients with asthma, eosinophilic airway inflammation is associated with poor lung function, increased disease severity, reduced quality of life and increased risk of exacerbations [1, 2]. As such, several biologic therapies targeting cytokines involved in eosinophil survival and activation have been developed, with the aim of reducing eosinophilic inflammation [3]. The response to these cytokine-targeting biologics has typically been assessed by monitoring clinical outcomes. Reductions in blood eosinophils have also been monitored [2], since these cells are easily accessible and are reflective of eosinophilic airway inflammation [4, 5]. However, the utility of sputum eosinophils as a biomarker for assessing the therapeutic response to biologic therapies remains an area of ongoing scientific debate and has been largely unexplored, owing to logistical challenges associated with their collection and measurement. In patients with severe eosinophilic asthma and sputum eosinophil counts of ≥3–<30%, sputum eosinophils may not represent a more useful biomarker than blood eosinophils for predicting clinical treatment response to mepolizumab https://bit.ly/3pOTw93